Occurrence of algal leaf spot on longan (Dimocarpus longan ) caused by Cephaleuros virescens in India - KUMAR, VINOD; ANAL, AJIT KUMAR DUBEDI; GUPTA, ALOK KUMAR; NATH, VISHAL (The Indian Journal of Agricultural Sciences, 2019)
Longan (Dimocarpus longan Lour. ) is an evergreen subtropical fruit tree species of Sapindaceae family with a long cultivation tradition in South East Asia. Between July to September of 2014 and 2015, leaves of longan trees were found infected by green algae at experimental farm of National Research Centre on Litchi, Muzaffarpur, Bihar (India). The symptoms of the disease appeared on the upper leaf surface as dark gray to reddish-rust coloured lesions, slightly raised with a velvet-like appearance. The disease incidence among leaves was 28. 4-57. 3% while percent disease severity index was 13. 3 to 20. 2. The algal thalli were isolated and cultured successfully on potato dextrose agar and Bold's basal medium but there was no development of sporangiophores and sporangia in culture. In pathogenicity test, inoculums either from naturally infected leaves or from pure culture of algal filaments could not reproduce typical symptom of the disease even up to three months of inoculation. Based on the leaf symptom and morphological characteristics, the pathogen was identified as Cephaleuros virescens Kunze. To our knowledge, this is the first report of leaf spots caused by Cephaleuros virescens on longan trees in India.